2021
DOI: 10.3390/su132111855
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Indoor Environment Quality of Indian School Classrooms

Abstract: The progress of Indoor Environmental Quality (IEQ) research in school buildings has increased profusely in the last two decades and the interest in this area is still growing worldwide. IEQ in classrooms impacts the comfort, health, and productivity of students as well as teachers. This article systematically discusses IEQ parameters related to studies conducted in Indian school classrooms during the last fifteen years. Real-time research studies conducted on Indoor Air Quality (IAQ), Thermal Comfort (TC), Aco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 277 publications
0
17
0
1
Order By: Relevance
“…Soft computing approaches have effectively been used in recent years to predict several important properties of RC structures and other different engineering applications [ 13 , 14 , 15 , 16 ]. ML algorithms are suitable for solving concrete-like complex problems and developing good relationships between input and output parameters.…”
Section: Application Of ML In Concrete Technologymentioning
confidence: 99%
“…Soft computing approaches have effectively been used in recent years to predict several important properties of RC structures and other different engineering applications [ 13 , 14 , 15 , 16 ]. ML algorithms are suitable for solving concrete-like complex problems and developing good relationships between input and output parameters.…”
Section: Application Of ML In Concrete Technologymentioning
confidence: 99%
“…Various studies around the globe found that airborne transmission is the prime cause of the rapid infection spread [12][13][14][15][16][17][18]22,[27][28][29][30][31]. To keep the economy growing, viral transmission concerns have been given increased attention in building facilities such as offices, schools, hotels, commercial buildings, hospitals, and other buildings.…”
Section: Introductionmentioning
confidence: 99%
“…It is well docu-mented that most of the 'super-spreading' cases where multiple people are found infected; occurred in closed spaces like offices, restaurants, schools, homes, building apartments, hospitals, assembly halls, etc. [12][13][14][15][16][17][18]. People spend the majority of their time indoors, and the quality of their indoor environment has a direct impact on their health [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Human health, performance, satisfaction, and productivity inside built environments are affected primarily by indoor environment quality (IEQ). Among major IEQ parameters like thermal comfort, acoustic comfort, and visual comfort, the indoor air quality (IAQ) is directly linked to sick building syndrome (SBS) which affects occupants' comfort and health negatively [1][2][3][4]. Generally, the most effective and usual method to improve IAQ is to bring in enough fresh air from outside [5].…”
Section: Introductionmentioning
confidence: 99%